How to Peer Review a Hypothesis - Without Killing It - Kenneth Markowitz; Kenneth Markowitz (Dental Hypotheses, 2010)
Dental hypothesis exists to provide the dental community with a forum for free thought and the expression of non-mainstream ideas. It is hoped that the thought provoking ideas expressed in this open access journal will lead to progress in both the scientific and clinical arenas. At first glance the idea of peer reviewing free thought may appear to be impossible. The reviewers and editorial team of Dental hypothesis can reconcile these goals by evaluating contributions for originality, plausibility, importance and clarity of expression. Although a hypothesis may reflect an author's point of view, valuable hypotheses reflect a balanced review of the literature and a reasonable grasp of the complexity of dental issues. Expert reviews are encouraged to challenge authors with alternative points of view while being respectful of the journal's mission to present ideas that many challenge existing paradigms.